Pediatric idiopathic hypercalciuria with bilateral nephrolithiasis and hypertensive urgency - Yolanda, Natharina; Irene, Irene (Universa Medicina, 2017)
BackgroundPediatric nephrolithiasis is an important cause of morbidity worldwide. Even with low prevalence, nephrolithiasis can cause detrimental long-term effects on kidney function. Idiopathic hypercalciuria is the most common cause of renal stones in children. This case report presents a pediatric patient with bilateral nephrolithiasis and hydronephrosis associated with underlying idiopathic hypercalciuria.Case descriptionWe report on a 17-month-old boy presenting with two days of high fever, irritability, nausea, and poor feeding. The patient had been diagnosed with bilateral nephrolithiasis at the age of 6 months. On examination, the patient was febrile and hypertensive. Laboratory evaluation revealed anemia, leukocytosis, normokalemia, normocalcemia, and normal glomerular filtration rate. Blood gases were within normal limits. Urinalysis revealed pH 5.0, hematuria, pyuria, and bacteriuria. Urine culture was positive for Proteus mirabilis and Enterobacter gergoviae. Electrolyte analysis from urine samples revealed hypercalciuria. Ultrasonography found stones at the left ureteropelvic junction with corresponding grade I hydronephrosis and stones in the right lower calyx without hydronephrosis. The patient was treated with antibiotics, an antihypertensive agent, thiazide diuretics, and was referred to a pediatric urologist.ConclusionThis case can be considered as idiopathic. Most children with renal stones have metabolic risk factors including enteric, endocrinologic, or renal sources. Metabolic evaluation is mandatory in pediatric renal stone patients and hypercalciuria is an important etiology to be evaluated. Ignorance of the underlying metabolic abnormality or failure in its identification in pediatric urolithiasis could lead to catastrophic long-term effects.